Evaluation of Dental Surface after De-Bonding Orthodontic Bracket Bonded with a Novel Fluorescent Composite: In Vitro Comparative Study - Marco Farronato; Davide Farronato; Francesco Inchingolo; Laura Grassi; Valentina Lanteri; Cinzia Maspero (Applied Sciences, 2021)
The use of a new fluorescent composite can reduce some of the problems related to procedures of de-bonding orthodontic bracket (enamel damage, dentine lesions, and composite residuals). The aim of the presented study was to compare the effect of fluorescent and conventional non-fluorescent composite on dental surface and composite remnants by in vitro de-bonding tests. De-bonding of florescent composite (DFC) and the de-bonding of standard composite (DSC) were performed by operators on an in vitro sample of 48 teeth under UV light (360–370 nm min 20 mW/cm2). Modified ARI (Adhesive Remnant Index), scored under 5.0×/235 magnification, was used for evaluation of dental surface after the procedure, and the duration required for de-bonding was measured. Significant differences in ARI between the two groups were observed (Pearson two-tailed p = 0.006 1.4 ± 0.1 95% C.I.), and the average duration of de-bonding was 38 s (DFC) and 77 s (DSC) per tooth, respectively (Mann–Whitney test p = 0.015; 57.7 ± 19.9 95% C.I.). The use of fluorescent composite could significantly improve the quality of de-bonding by reducing the quantity of composite residuals and visible enamel damage, while reducing time needed for successful procedure performance.